0522 A Novel Wake-sensing CPAP Technology For Patients With PTSD And OSA. (27th April 2018) - Holley, A B; Terry, S; Shaha, D; Robertson, B; Andrada, T; Collen, J
Abstract: Introduction: OSA is common in PTSD, often confounded by poor CPAP adherence with diminished response to therapy. Sensawake is a wake-sensing CPAP algorithm that lowers pressure when wake is detected. We compared CPAP with and without Sensawake for co-morbid OSA/ PTSD. The primary outcome was CPAP adherence at four and eight weeks. Secondary outcomes assessed sleep symptoms. Methods: This is a prospective, randomized, single blind, crossover study, comparing standard autoCPAP to autoCPAP with Sensawake. We enrolled OSA/PTSD patients who were CPAP naïve. Four weeks after randomization, patients crossed over to the other treatment group, with final follow-up at eight weeks. Patients completed clinical sleep questionnaires (ESS, ISI, FSS, FOSQ-10) at baseline and follow-up. Results: We enrolled 85 patients with PTSD/OSA newly initiating CPAP. 54 subjects completed the study. The population was predominantly male with mild OSA and groups were similar at baseline. CPAP reduced the AHI effectively to <5/h in both groups. Intention to treat analysis (ITT) of Sensawake, adjusted for differences in ESS at baseline and PAP leak, was associated with significant increase in hours used per total nights ( ß = 1.28 (95% CI: 0.02 - 2.54); p = 0.047), and trends toward improvements in hours per nights used ( ß = 0.89 (95% CI: -0.03 - 1.8); p = 0.057), percentage nights used ( ß = 17.2 (95% CI: - 2.2 - 36.6); p = 0.08) percentage nights used > 4 hours ( ß = 16.8 (95% CI: - 2.6 - 36.2); p = 0.09) and adequate adherence (OR = 6.9 (95% CI: 0.7 - 61.8); p =0.09). ESS, ISI, and FSS decreased by 3.0 ± 5.0 (p < 0.001), 4.7 ± 4.5 (p < 0.001), and 8.2 ± 11.1 (p < 0.001) respectively. The FOSQ10 increased by 4.3 ± 7.4 (p = 0.001). There were no differences in magnitude of improvement in any score between groups. Conclusion: Adherence to CPAP with Sensawake is significantly improved compared to standard therapy. Sensawake is non-inferior to standard care for normalizing the AHI and improving sleep related symptoms and quality of life. Support (If Any): None.